Change of Tropism of SL3-2 Murine Leukemia Virus, Using Random Mutational Libraries - Bahrami, Shervin (American Society for Microbiology, 2004)
SL3-2 is a polytropic murine leukemia virus with a limited species tropism. We cloned the envelope gene of this virus, inserted it into a bicistronic vector, and found that the envelope protein differs from other, similar envelope proteins that also utilize the polytropic receptor (Xpr1) in that it is severely impaired in mediating infection of human and mink cells. We found that two adjacent amino acid mutations (G212R and I213T), located in a previously functionally uncharacterized segment of the surface subunit, are responsible for the restricted tropism of the SL3-2 wild-type envelope. By selection from a two-codon library, several hydrophobic amino acids at these positions were found to enable the SL3-2 envelope to infect human TE 671 cells. In particular, an M212/V213 mutant had a titer at least 6 orders of magnitude higher than that of the wild-type envelope for human TE 671 cells and infected human, mink, and murine cells with equal efficiencies. Notably, these two amino acids are not found at homologous positions in known murine leukemia virus isolates. Functional analysis and library selection were done on the basis of sequence and tropism analyses of the SL3-2 envelope gene. Similar approaches may be valuable in the design and optimization of retroviral envelopes with altered tropisms for biotechnological purposes.